Macroeconomic conditions and capital structure adjustment speed - Cook, Douglas O.; Tang, Tian (Journal of Corporate Finance, 2010)
Using two dynamic partial adjustment capital structure models to estimate the impact of several macroeconomic factors on the speed of capital structure adjustment toward target leverage, we find evidence that firms adjust their leverage toward target faster in good macroeconomic states relative to bad states. This evidence holds whether or not firms are subject to financial constraints. Our results are robust to an alternative method of calculating states and to omitting zero-debt boundary firms and are not driven by firm size, deviation from target, or leverage definitions.